2023
DOI: 10.3390/plants12081667
|View full text |Cite
|
Sign up to set email alerts
|

LED Lighting to Produce High-Quality Ornamental Plants

Abstract: The flexibility of LED technology, in terms of energy efficiency, robustness, compactness, long lifetime, and low heat emission, as well as its applications as a sole source or supplemental lighting system, offers interesting potential, giving the ornamental industry an edge over traditional production practices. Light is a fundamental environmental factor that provides energy for plants through photosynthesis, but it also acts as a signal and coordinates multifaceted plant-growth and development processes. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 105 publications
0
6
0
1
Order By: Relevance
“…However, plants have five different photoreceptors that can detect light outside the PAR range. Research has shown that UV-A radiation can increase plant vigor and affect leaf pigments, while IR radiation can affect the flowering cycle [24][25]. In contrast, the Vlambda curve shows the different light sensitivities of humans, with our visual system being most sensitive to green-yellow light (Figure 2).…”
Section: The Sensitivity To Light Differs Between Plants and Humansmentioning
confidence: 99%
“…However, plants have five different photoreceptors that can detect light outside the PAR range. Research has shown that UV-A radiation can increase plant vigor and affect leaf pigments, while IR radiation can affect the flowering cycle [24][25]. In contrast, the Vlambda curve shows the different light sensitivities of humans, with our visual system being most sensitive to green-yellow light (Figure 2).…”
Section: The Sensitivity To Light Differs Between Plants and Humansmentioning
confidence: 99%
“…Electric lighting has been increasingly used for controlled environment production of ornamental plants [5,6]. There are different ways to apply electric lighting in production such as night interruption lighting, day extension lighting, supplemental lighting, and sole-source lighting, for different production purposes.…”
Section: Application Of Electric Lighting To Manipulate Bl In Ornamen...mentioning
confidence: 99%
“…Chrysanthemums are quantitative short-day plants that flower uniformly when the critical day-length photoperiod is ≈13.5 h or less but fail to flower under longer photoperiods than the critical day length [31]. The grading standards for cut chrysanthemum on the world market require an elongated and unbranched plant shape and large-sized flowers [5]. Due to the required stem length specification in cut chrysanthemum production, artificially long days are maintained routinely for 2-3 weeks before the onset of short days [31].…”
Section: Bl Alonementioning
confidence: 99%
“…Blue light enhances the chl a/b ratio and photosynthesis rate [ 25 ] and controls stomatal opening and the biosynthesis of secondary metabolites [ 26 , 27 , 28 ], while inhibiting cell division and extension of growth [ 23 ]. Horticulture plant quality takes advantage of LED lighting to shape plant architecture, induce flowering, prevent postharvest loss, and enhance flower and leaves pigmentation [ 29 ].…”
Section: Morphological Traits Regulation By Led Spectrum Qualitymentioning
confidence: 99%